Metodologia de implantação da construção enxuta: estudo de caso em construtora de porte médio - Oliveira, Erikson Ricardo Marques de (2013)
In recent years, the Brazilian construction industry has gone by changes like currency stability, increasing competition, shortage of skilled labor and increasing quality importance required by the customer, who made the sector companies seek solutions through new management practices in order to become more efficient. A alternative to these management practices is known as Lean Construction which is derived from the Toyota System Production. Lean Construction main goals are to reduce parts of activities that do not add value, increase product value by considering customer needs, reduce variability and production cycle time, simplify process by reducing the number of parts or steps, increase the flexibility in the product execution and transparency process, focus the control on overall process, introduce continuous improvement process, maintain a balance between improvements in flows and conversions and seek to learn from practices adopted by competitors. However, the construction industry is characterized by having nomadic activity, which undertakes an unique product with high cost of production and big inertia for behavioral change, making it difficult to implement the philosophy of lean construction in companies. In this sense, the main objective of this study is to develop a methodology for implementation of the principles of Lean Construction. The method of implementing the proposed management system was designed with the aid of 5W2H tool, and the implementation process is divided into three phases. The first one aims to know in a macro way the current operation of construction, identify who is its target audience and what are the products and services offered to the Market. The second phase aims to describe what actions should be taken and which documents are needed to be created or modified; finally, the third step goal consists in how to control and monitor established processes, where through Strategic Planning the company goals would be set along with their respective targets and indicators in order to keep the system working, aiming for continuous improvement with focus on the customer. This methodology was conceived as a case study analyzing a medium size construction with more than 18 years of activity and certified for almost 10 years with ISO9001 and level A in PBQP-H. We also conclude that this implementation process can be used in any developer and / or builder